Multidisciplinary Approach for Full-Mouth Rehabilitation of a Young Adult Patient with Ameloblastoma - Hung-Yi Liao; May-Show Chen; Ya-Fen Yang; Pei-Bang Liao; Sheng-Wei Feng; Po-kai Juan (Case Reports in Dentistry)
Ameloblastoma is a benign but locally invasive neoplasm of the odontogenic epithelium that tends to grow slowly in the mandible or maxilla. It can be highly destructive to the surrounding dental anatomy and can cause death by progressive spread to nearby vital structures in rare cases. Marginal resection is the most effective method of eliminating the tumor, but treatment can further contribute to oral and dental deformity and malfunction. This clinical report describes the dental rehabilitation of a young adult patient diagnosed with ameloblastoma and underwent preliminary marsupialization, segmental mandibulectomy, and fibula free flap reconstruction, followed by mandibular dental implant placements. Orthodontic and rapid palatal expansion for maxillary arch correction was also performed. The treatment goal of regaining dental function and a satisfactory appearance was accomplished.